Surface-selective laser sintering of thermolabile polymer particles using water as heating sensitizer. (November 2015) - Antonov, E.N.; Krotova, L.I.; Minaev, N.V.; Minaeva, S.A.; Mironov, A.V.; Popov, V.K.; Bagratashvili, V.N.
Abstract: We report the implementation of a novel scheme for surface-selective laser sintering (SSLS) of polymer particles, based on using water as a sensitizer of laser heating and sintering of particles as well as laser radiation at a wavelength of, corresponding to the strong absorption band of water. A method of sintering powders of poly(lactide-co-glycolide), a hydrophobic bioresorbable polymer, after modifying its surface with an aqueous solution of hyaluronic acid is developed. The sintering thresholds for wetted polymer are by lower than those for sintering in air. The presence of water restricts the temperature of the heated polymer, preventing its thermal destruction. Polymer matrices with a developed porous structure are obtained. The proposed SSLS method can be applied to produce bioresorbable polymer matrices for tissue engineering.